1999
DOI: 10.1037/0096-1523.25.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Stroop and Garner effects in comparative judgment of numerals: The role of attention.

Abstract: In 7 experiments, participants selected the larger member of pairs of digits that differed in numerical magnitude as well as in physical size. Selective attention to the relevant dimension (number or size) was gauged by Garner and Stroop interference, both of which varied considerably as a function of the number and relative discriminability of values along the constituent dimensions. When the to-be-ignored dimension was more discriminable, sizable Garner and Stroop effects affected performance on the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 59 publications
14
145
3
Order By: Relevance
“…A more convincing finding would be that numerical and non-numerical quantities interact with each other. This is exactly what is found with the size congruity paradigm (Algom et al, 1996;Cohen Kadosh and Henik, 2006;Cohen Kadosh et al, 2007e;Fias et al, 2002;Henik and Tzelgov, 1982;Hurewitz et al, 2006;Pansky and Algom, 1999;Schwarz and Ischebeck, 2003;Tzelgov et al, 1992). In this Stroop-like task, numerical and physical dimensions are varied independently.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thsupporting
confidence: 72%
See 2 more Smart Citations
“…A more convincing finding would be that numerical and non-numerical quantities interact with each other. This is exactly what is found with the size congruity paradigm (Algom et al, 1996;Cohen Kadosh and Henik, 2006;Cohen Kadosh et al, 2007e;Fias et al, 2002;Henik and Tzelgov, 1982;Hurewitz et al, 2006;Pansky and Algom, 1999;Schwarz and Ischebeck, 2003;Tzelgov et al, 1992). In this Stroop-like task, numerical and physical dimensions are varied independently.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thsupporting
confidence: 72%
“…As previously mentioned in the behavioral section of this review, a different task that might be used to examine the uniqueness of numbers is the size congruity task (Cohen Kadosh and Henik, 2006;Cohen Kadosh et al, 2007e;Henik and Tzelgov, 1982;Pansky and Algom, 1999;Schwarz and Ischebeck, 2003;Tzelgov et al, 1992). The slowing down of responses (i.e., the size congruity effect) by the irrelevant dimension suggests that processing of numerical and physical dimensions overlap up to a certain point, when selection of the relevant dimension occurs.…”
Section: Evidence For Overlap In the Neural Code For Different Magnitmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the numerical values chosen were scaled versions of actual bar lengths that, when struck, would produce the particular frequencies. Third, Pansky and Algom (1999) used the Garner interference paradigm and demonstrated that numerical magnitude and physical size are perceptually integral.…”
Section: Methodsmentioning
confidence: 99%
“…Tests of cross-dimensional relationships often manipulate more levels of one dimension than of the other, creating an imbalance in discriminability (see Pansky & Algom, 1999). In the space-time experiments by Casasanto & Boroditsky (2008), however, there were 9 levels of each dimension fully crossed, to equate discriminability.…”
Section: Introductionmentioning
confidence: 99%